Comparison of the Asymmetries in Foot Posture and Properties of Gastrocnemius Muscle and Achilles Tendon Between Patients With Unilateral and Bilateral Knee Osteoarthritis - Chen, Zehua; Ye, Xiangling; Shen, Zhen; Wang, Yi; Wu, Zugui; Chen, Guoqian; Guan, Yingxin; Wu, Jiatao; Jiang, Tao; Wu, Huai; Liu, Wengang; Xu, Xuemeng (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Asymmetrical foot posture and properties alterations of gastrocnemius muscle (GM) and Achilles tendon (AT) were observed in knee osteoarthritis (KOA). We aimed to investigate the inter-limbs asymmetries in foot posture and the properties of GM and AT, and explore the association between them. Methods: A total of 62 subjects with unilateral or bilateral KOA were included in this study, 30 patients with unilateral pain and 32 patients with bilateral pain were assigned to the bilateral group (BG) and unilateral group (UG) respectively, and the relatively serious leg (RSL) and relatively moderate leg (RML) were judged according to the severity of symptoms assessed by using VAS (visual analogue scale) motion. Foot posture and asymmetrical foot posture scores were assessed based on foot posture index (FPI-6). Subsequently, all the participants were tested with MyotonPRO (Estonia) for properties of GM and AT including tone (Hz), stiffness (N/m) and elasticity. We calculated the asymmetry index of AT (Asy-AT) in both legs and the difference of muscle properties betwen medial and lateral gastrocnemius (D-MLG) in the ipsilateral limb. Results: Asymmetry of foot posture was categorized into 3 types including normal, asymmetry, and severe asymmetry, while the percentage of subjects classified as the normal was higher in the BG than the UG; tone of AT and lateral gastrocnemius (LG) in RSL were higher than those in RML, and stiffness of AT in the RSL were larger than RML. Meanwhile, a positive relationship was found between ipsilateral FPI and tone of MG and LG in the left and right legs, whereas there was a positive link between asymmetrical FPI scores and K/L grade. Furthermore, a significantly greater Asy-AT(tone) was detected in the UG than that in the BG. Additionally, an increased asymmetrical FPI score (i.e., more severe asymmetry) was significantly associated with increases in Asy-AT(tone) and Asy-AT(stiffness). Conclusions: Patients with bilateral KOA presented a more asymmetrical foot posture and AT tone. Considering the relationship between FPI and properties of AT and GM, correcting the asymmetries in foot posture or the properties of AT and GM could be beneficial to improve KOA.